Self-assembly of defined core–shell ellipsoidal particles at liquid interfaces - Eatson, Jack; Bauernfeind, Susann; Midvedt, Benjamin; Ciarlo, Antonio; Menath, Johannes; Pesce, Guiseppe; Schofield, Andrew B.; Volpe, Giovanni; Clegg, Paul S.; Vogel, Nicolas; Buzza, D. Martin A.; Rey, Marcel (Journal of Colloid and Interface Science, 2025)
Hypothesis: Ellipsoidal particles confined at liquid interfaces exhibit complex self-assembly due to quadrupolar capillary interactions, favouring either tip-to-tip or side-to-side configurations. However, predicting and controlling which structure forms remains challenging. We hypothesize that introducing a polymer-based soft shell around the particles will modulate these capillary interactions, providing a means to tune the preferred self-assembly configuration based on particle geometry and shell properties. Experiments: We fabricate core–shell ellipsoidal particles with defined aspect ratios and shell thickness through thermo-mechanical stretching. Using interfacial self-assembly experiments, we systematically explore how aspect ratio and shell thickness affect the self-assembly configurations. Monte Carlo simulations and theoretical calculations complement the experiments by mapping the phase diagram of thermodynamically preferred structures as a function of core–shell properties. Findings: Pure ellipsoidal particles without a shell consistently form side-to-side “chain-like” assemblies, regardless of aspect ratio. In contrast, core–shell ellipsoidal particles exhibit a transition from tip-to-tip “flower-like” arrangements to side-to-side structures as aspect ratio increases. The critical aspect ratio for this transition shifts with increasing shell thickness. Our results highlight how we can engineer the self-assembly of anisotropic particles at liquid interfaces by tuning their physicochemical properties such as aspect ratio and shell thickness, allowing the deterministic realization of distinct structural configuration
Keywords: Liquid interfaces; Core-shell polymeric ellipsoidal particles; Capillary interactions; Anisotropic particle; Self-assembly; Phase behaviour